A Novel Highly Selective "Turn‐On" Fluorescence Sensor for Silver Ions Based on Schiff Base. Issue 12 (7th November 2014) - Lin, Qi; Yang, Qingping; Sun, Bin; Wei, Taibao; Zhang, Youming
Abstract A novel optical chemical sensor L was designed and synthesized for the determination of silver ions. The sensor L was derived from 1‐naphthaldehyde and 3, 4, 5‐tris(hexadecyloxy)benzohydrazide. The sensor L shows high sensitivity and selectivity for Ag+ detection in comparison to other metal cations (Mg2+, Ca2+, Al3+, Cr3+, Fe3+, Co2+, Ni2+, Cu2+, Zn2+, Cd2+, Hg2+, Pb2+) and has no significant response to other common metal cations. Upon addition of Ag+, the fluorescent emission of the sensor L was enhanced dramatically but other metal cations had no same response. The detection limit for Ag+ was 1.2×10−7 mol/L. Therefore, the sensor L is useful for Ag+ detection with some advantages including sensitivity, selectivity, simplicity and low‐cost.